Development of optical sensor material for detection of cadmium using alizarin-red s indicator / Wan Elina Faradilla Wan Khalid and Nurul Farahidora Jaafar - Wan Khalid, Wan Elina Faradilla; Jaafar, Nurul Farahidora (Universiti Teknologi MARA Cawangan Pahang, 2020)
In this study, Alizarin Red S (ARS) reagent was used to detect cadmium (Cd2+) in solution by using UV-Visible Spectrophotometer. Six parameters have been studied which are the effect of pH, effect of ARS concentration, photostability, linear range, reproducibility and interference study. ARS reagent form complex with Cd2+ and showed a maximum absorption at 424.50 nm in pH 6. Under optimized conditions, ARS reagent was able to detect the concentration of Cd2+ in the range of 0 - 5 ppm. The reproducibility study gives RSD values of 1.23% and 2.89% for the concentration of 1 ppm and 5 ppm, respectively. From this study, Fe3+ was found to interfere the most during the Cd2+ determination followed by Ni2+, Hg+ and Cu2+. The immobilization of the ARS reagent was conducted by using three immobilization matrix which is sol-gel, polyvinyl alcohol (PVA) and hybrid sol-gel/PVA. The finding suggested that the hybrid sol-gel/PVA can improve the leaching problem of the ARS reagent